Development of operational construction management in modern conditions - Matviievskyi, S.V.; Klys, M.V. (Ways to Improve Construction Efficiency, 2021)
The article highlights the problems that arise in the management process, during the construction of buildings and structures. Operational management is an important part of a single planning system for construction production and has the following ultimate goals: the implementation of tasks for the commissioning of facilities; volume of construction and installation works; increasing labor productivity, etc. The function of operational management includes a continuous impact on the timely implementation of the work provided for in the plan. The stage of operational management includes operational planning and regulation, which includes control, accounting and decision-making. In the process of production, any management decisions related to the implementation of the project are reduced to the establishment of calendar modes of work. When making plans for a long period, it is impossible to take into account all the factors that may arise in the period immediately preceding the start of work. As we approach the planned deadlines, awareness of the specific situation is constantly growing. In modern conditions, in the absence of permanent labor collectives in construction organizations, to the previously defined functions of operational planning should be added the function of providing construction with skilled labor. Creating a network of operational management in accordance with the production program of the construction organization, its structure, possible customer requirements, with the use of modern software packages to significantly improve the quality of operational management in construction. Changes in the process of operational management of construction production should be aimed primarily at eliminating backlogs in the implementation of weekly and daily work schedules. To do this, depending on the causes of the backlog, measures are taken to speed up the work, introduce additional changes, eliminate interruptions in the material support of the work and other measures.